IMPLEMENTASI PASAL 5 PERATURAN DAERAH KABUPATEN PASURUAN NO.11 TAHUN 2005 TENTANG PENATAAN DAN PEMBINAAN KEGIATAN PEDAGANG KAKI LIMA YANG MENGATUR TENTANG DAFTAR USAHA (di Desa warung Dowo Kec. pohjentrek Kab. Pasuruan) - dian mustafida (Dinamika, 2021)
The rise of street vendors throughout Indonesia cannot be denied until now. Especially area in KAb. Pasuruan, which is an industrial area and street vendors are one of the informal sectors that dominate area in Kab. Pasuruan. One area in Kab. Pasuruan whose area is vulneranle to use by streer vendors to sell, is in the area along Jalan Raya Warung Dowo Village. Where the highway is the main road that is passed to get out of the Regency/ City both from Malang-Pasuruan-Probolinggo or vice versa. So that sometimes the streets become jammed and the city order becomes chaotic because the traders who sell do not comply with the rules. Because there is no Indonesian regulation that specifically regulates street vendors, the Regional Government issues a Regional Regulation, namely, the Kabupaten Pasuruan Regional Regulation No. 11 of 2005 concerning Structuring and Guiding Street Vendor Activites.Keywords: Street vendors, along the higway, local regulation, Kab. Pasuruan.